Cómo conquisté a los aztecas - Cortés, Hernán, 1485-1547; Ayala Anguiano, Armando, 1928-2013 (Mexico : Editorial Diana, 1990)
Tomado de la contracubierta
Incluye índice.
Keywords: CORTES, HERNAN, -- 1485-1547 -- CORRESPONDENCIA, MEMORIAS, ETC; AZTECAS; MEXICO -- HISTORIA -- CONQUISTA, 1519-1540